Community Participation And Rural Development Sustainability In Some Selected Communities Of Edo State, Nigeria - Ebonine, Victor; Kadiri, John Aigboje (Brawijaya Journal of Social Science, 2026)
Addressing rural underdevelopment has been a major challenge to the Nigerian government since independence.  To that extent, previous initiatives were created to address it. However, they failed to yield the desired positive outcomes, necessitating further refinement of robust initiatives that would address this challenge, until the Community and Social Development Projects (CSDPs) were established. This initiative was designed to address the challenge that the previous initiatives encountered, namely, centrism that obscured community participation and project sustainability. This study, therefore, aimed to examine the extent to which communities participated in the CSDPs and whether their participation contributed to project sustainability in Edo State, Nigeria. The study utilised an in-depth interview method to elicit responses from 109 participants across the selected communities in the state. The study found that the communities were involved in both the planning and implementation stages of the project execution. Their involvement translated into efforts at sustaining the projects, namely in providing funds and manual skills such as clearing weeds around the projects and cleaning and maintaining them. The study, therefore, recommends that there should be sustainable mechanisms for checking continued maintenance of projects, greater government involvement in project sustainability, and improved and sustained women's involvement in community participation in CSDP in rural communities of Edo State, and by extension, Nigeria.